A polyimide-free configuration for tunable terahertz liquid-crystal-based metasurface with fast response time. (June 2023) - Deng, Guangsheng; Mo, Haisheng; Kou, Zhifei; Yang, Jun; Yin, Zhiping; Li, Ying; Lu, Hongbo
Highlights: A polyimide-free configuration for tunable liquid–crystal-based metasurface is proposed. A fully electrically controlled method to re-orient the liquid crystal molecules is experimentally demonstrated. Dynamically and continuously tuning of resonance peak frequency can be achieved with the proposed strategy. The response is increased by one order of magnitude compared with traditional LC metasurfaces with a polyimide layer. Abstract: This paper proposes a method for reorientation of the liquid crystal (LC) molecules with a fully electrically controlled method and demonstrates its application in simplifying the metasurface preparation and shortening the response time of LC devices at terahertz frequency band. By incorporating the interdigitated electrodes and applying different bias voltages to adjacent fingers, the permittivity of LC material, which is closely related to the orientation of the molecules, can be dynamically tuned from minimum to maximum. The polyimide (Pi) film has an indispensable role in the initial orientations of the LC molecules in traditional LC metasurfaces. However, the transverse electric field generated by the interdigitated electrodes helps the LC molecules orientation and the Pi film is not required in the design, which greatly simplifies the structure and fabrication process of the device. Meanwhile, the proposed strategy overcomes major shortcomings like complex processing and slow relaxation time brought in by the Pi alignment layer in most of the reported LC devices. The experimental results show that the response of the proposed LC metasurfaces was increased by one order of magnitude compared with traditional LC metasurfaces.